Development, in-vitro and in-vivo evaluation of gentamicin and Nigella sativa oil PLGA microspheres - Ahmad Fahmi Harun Ismail (Kulliyyah Pharmacy, International Islamic University Malaysia, 2017)
Introduction: Antibiotics are amongst the highly studied and researched candidates for sustained drug release formulation. In this current study, gentamicin was formulated in the form of microspheres using poly(lactic-co-glycolic acid) (PLGA) to be used as prophylactic approach in eradicating osteomyelitic condition in rabbits. Together with Nigella sativa oil (NSO) where its potentials are well known, the ability of the PLGA microspheres loaded with gentamicin and NSO was evaluated for in-vitro and in-vivo studies. Objective: The main objective of this study was to formulate a sustained release microspheres containing gentamicin and NSO intended to treat osteomyelitis. Methodology: Gas chromatography mass spectrometry (GC-MS), high performance liquid chromatography (HPLC), Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), thin layer chromatography (TLC) and cell viability study (MTT assay) were utilized to evaluate the compatibility as well as the stability for pre and post gamma irradiation. 27 formulations for both gentamicin and NSO microspheres were fabricated. Other than observing the external morphology of the microspheres using scanning electron microscope (SEM), the size distributions were also being analyzed. For quantification purposes, two method validations were completed by using UV-spectrophotometry following the requirements listed under ICH Q2 (R1) guidelines. For the in-vivo study, 16 White New Zealand rabbits were divided into 4 groups (Control, Gentamicin, NSO and Fusion) before the osteomyelitic condition was induced in the tibiae of the animals. The compressed selected microspheres were administered in-situ and all the animals were closely monitored for any physiological changes over a course of 6 weeks. X-ray images, hematological evaluation (white blood cell differentiations) and post surgical bacterial culture were evaluated to confirm the prophylactic ability of the microspheres to halt the infection. Results: The size distribution ranging from 463.67 nm ± 52.54 to 4602 nm ± 113.58 and 409.67 nm ± 37.45 to 6568.00 nm ± 147.22 for gentamicin and NSO microspheres respectively. Five best formulations from gentamicin and NSO microspheres with the highest drug loading capacity (ranging from 67.32% ± 3.18 to 83.39% ± 4.22 for gentamicin microspheres and from 62.94% ± 4.84 to 73.42% ± 2.14 for NSO microspheres) were further analysed for the in-vitro release profile over a course of 4 weeks study. The best formulation was selected from gentamicin microspheres and NSO microspheres based on the in-vitro release data before being used for in-vivo study (compressed microspheres from formulation 6 for both gentamicin and NSO group). Conclusion: Based on the data collected with 95% confidence level (p<0.05), gentamicin and NSO microspheres indicated the ability to treat osteomyelitis when compared to the untreated group. The replacement of current conventional treatment using PMMA beads is possible by the microspheres fabricated.